Anisotropic mesoporous germanium nanostructures by fast bipolar electrochemical etching. (10th May 2021) - Dupuy, Arthur; Aziziyan, Mohammad Reza; Machon, Denis; Arès, Richard; Boucherif, Abderraouf
Abstract: Mesoporous germanium has received lately a growing interest in many fields. However, the lack of flexibility and knowledge concerning its electrochemical etching remains important. In this study, it is demonstrated the first synthesis of anisotropic porous morphologies using fast bipolar electrochemical etching (FBEE). The influence of the total porosification time, the etching density as well as the passivation time on the formation of tubular porous Ge (T-PGe) are investigated. It is also shown that is possible to modify T-PGe morphology by chemical etching to create Columnar Porous Germanium (C-PGe) that offers more opened porosity with lower specific surface area. Furthermore, we report the advantage of the electrochemical performances of C-PGe compared to T-PGe, when used as on-chip anodes for lithium-ion battery. Our findings demonstrate that by engineering the porous Ge morphology the cycle life of produced anodes could be extended by a factor 26 and 1.8 for high rate and high energy applications, respectively.